1998
DOI: 10.2466/pms.1998.87.3.1003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High and Moderate Intensity of Strength Training on Mood and Anxiety in Older Adults

Abstract: This study was designed to examine the psychological benefits of anaerobic exercise for older adults. Specifically, strength training was employed to examine the effects on mood and anxiety in a group of healthy but sedentary older women. 36 women (mean age = 68.5 yr.) were randomly assigned to groups given high intensity or moderate intensity strength training or to a control group. Strength training was conducted three days a week for 12 weeks. After the training period, both high and moderate strength-train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 19 publications
3
35
0
1
Order By: Relevance
“…While depression was reduced following aerobic training according to this study, it was not altered following strength training. In contrast, the studies by Singh et al [66][67][68], Tsutsumi et al [74], and Cassilhas et al [17] were unequivocal in indicating improvement both in strength and in mood and depression. Further, one of the Singh et al studies [67] reported that the antidepressant effect of exercise was maintained over 20 weeks when laboratory-based supervised exercise was changed to unsupervised patient-directed weight lifting in gym or home settings.…”
Section: Studies Applying Strength Trainingmentioning
confidence: 86%
See 3 more Smart Citations
“…While depression was reduced following aerobic training according to this study, it was not altered following strength training. In contrast, the studies by Singh et al [66][67][68], Tsutsumi et al [74], and Cassilhas et al [17] were unequivocal in indicating improvement both in strength and in mood and depression. Further, one of the Singh et al studies [67] reported that the antidepressant effect of exercise was maintained over 20 weeks when laboratory-based supervised exercise was changed to unsupervised patient-directed weight lifting in gym or home settings.…”
Section: Studies Applying Strength Trainingmentioning
confidence: 86%
“…These studies varied in the length of the intervention. For example, while the study of Cassilhas et al [17] reported improvement after 24 weeks, the Singh et al [68] study was able to demonstrate improvement after 8 weeks and Tsutsumi et al [74] after 12 weeks. One study [20] did not report any emotional alterations following 8 weeks of resistance training.…”
Section: Studies Applying Strength Trainingmentioning
confidence: 97%
See 2 more Smart Citations
“…Notably, research supports increases in strength are linked to improved psychological health such as reduced anxiety [7] , reduced depression [8] , and improved self-esteem [9] ; all factors in the GHQ (questions 2; 9; 10 & 11, respectively). It would be interesting to know if there is a cause and effect relationship between participation, or specifically strength increases.…”
Section: Dear Editormentioning
confidence: 99%